Fatty acid metabolism in the freshwater fish Murray cod (Maccullochella peelii peelii) deduced by the whole-body fatty acid balance method - Giovanni Turchini; David Francis; S De Silva (2006)
The whole-body fatty acid balance method was used to investigate the fatty acid metabolism in Murray cod (Maccullochella peelii peelii) fed diets containing canola (CO) or linseed oil (LO). Murray cod were able to elongate and desaturate both 18 : 2n − 6 and 18 : 3n − 3. In fish fed the CO diet, 54.4% of the 18 : 2n − 6 consumed was accumulated, 38.5% oxidized and 6.4% elongated and desaturated to higher homologs. Fish fed the LO diet accumulated 52.9%, oxidized 37% and elongated and desaturated 8.6% of the consumed 18 : 3n − 3. The overall roles of n − 6 fatty acids appeared more important in Murray cod compared to other freshwater species. Murray cod also showed a preferential order of utilization of C18 fatty acid for energy production (18 : 3n − 3 > 18 : 2n − 6 > 18 : 1n − 9). Moreover, it is demonstrated that an increase in dietary 18 : 3n − 3 is directly responsible of increased desaturase activity and augmented saturated fatty acid accumulation in the fish body. The present study also suggests that, in the context of the possible maximization of the natural ability of fish to produce long chain polyunsaturated fatty acids, the whole-body approach can be considered well suited and informative and Murray cod is a suited candidate to fish oil replacement for its diets.